Analysis of surface drag over Antarctic sea ice from High-Resolution measurements from Terrestrial Laser Scanning and Large Eddy Simulations - Trujillo Gomez, Ernesto; Giometto, Marco Giovanni; Leonard, Katherine Colby; Maksym, Ted L.; Meneveau, Charles V.; Parlange, Marc; Lehning, Michael (2015)
Sea ice/snow surface interactions with the atmosphere are major drivers of large-scale patterns of sea ice flows and deformations in Polar Regions. Climate and weather prediction models require parameterizations of the subgrid-scale surface drag caused by the interactions between the ice/snow surfaces and surface winds. Here, we combine the analysis of sea ice/snow surface topography at very high-resolutions (~1-10 cm), local wind measurements, and Large Eddy Simulations (LES) of fully developed wind flow to study surface drag and roughness from process scales to floe scales (~ 1 cm – 100 m). The snow/ice elevations were obtained using a Terrestrial Laser Scanner (TLS) during the SIPEX II (Sea Ice Physics and Ecosystem eXperiment II) research voyage to East Antarctica (September-November 2012). LES are performed on a regular domain adopting a mixed pseudo-spectral/finite difference spatial discretization. A scale-dependent dynamic subgrid-scale model based on Lagrangian time averaging is adopted to determine the eddy-viscosity in the bulk of the flow. The effects of large-scale features of the surface on wind flows (those features that can be resolved in the LES) are accounted for through an immersed boundary method. Conversely, drag forces caused by subgrid-scale features of the surface should be accounted for through a parameterization. However the effective aerodynamic surface roughness parameter z0 for snow/ice is not known. Hence, a dynamic approach is utilized, in which this parameter is determined using the first-principles based constraint that the total momentum flux (drag) must be independent on grid-filter scale. LES are performed over fine scans of typical surface structures, and over larger domains filtered at coarser grid resolutions (~ 1 m). A total of six ice floes are studied, with before and after-storm TLS data at one of the floes for an analysis of the changes in the surface structure and its effects on the surface-atmosphere interactions. The spatial distributions of friction velocities ...